Prediction of emotional exhaustion over the course of the COVID-19 pandemic in primary care dental staff: an intensive longitudinal study. Issue 12 (30th December 2021) - Freeman, Ruth; Knights, Jennifer; Beaton, Laura; Araujo, Mariana; Yuan, Siyang; Clarkson, Jan; Young, Linda; Humphris, Gerald
Abstract : Objective: To investigate the fatigue trajectory during a 6-month duration of the COVID-19 pandemic for dental health professionals in primary dental care and for those in training. Design: A longitudinal intensive panel diary was conducted (July–December 2020) assessing weekly self-ratings of emotional fatigue. Setting: Dental care services in Scotland. Participants: Dental trainees and primary dental care staff (N=53). These data were merged with respondents' replies to a cross-sectional baseline survey (Humphris et al ). Recruitment was through 'Portal', an online tool administered by National Health Service Education for Scotland. Questback software was employed for data collection. Primary and secondary outcome measures: The diary questionnaire, consisted of a three-item fatigue scale and, from the baseline survey, three multi-item scales including: preparedness (14 items of the Dental Professional Preparedness for Practice Scale), the 22-item Impact of Event Scale-Revised and depressive symptomatology using the Patient Health Questionnaire-2. Statistical analysis included estimating the variability of fatigue over the study duration using a multilevel linear growth model. In addition, a path analysis was performed to determine the ability of preparedness and COVID-19 pandemic trauma to predict fatigue trajectories directly, or mediated through depressive symptomatology. Results: A large variation of fatigue trajectories (p<0.001) was found from staff who completed a mean of 11 weekly uploads of their diary (diary uploads: minimum 4–maximum 24). The average slope was positive (standardised estimate=0.13, 95% CI: 0.07 to 0.19, p<0.001). Slope variation was modelled successfully from baseline data showing direct and indirect effects from preparedness, trauma and depressive symptoms. Conclusion: Staff who volunteered to participate over a significant period of the COVID-19 pandemic in Scotland displayed a highly significant variety of individual trajectories. The results show some consistency with a job demands-resources model of burnout development. Suitable resource structures are indicated for staff over periods of extensive public service change.